Significance of the combination of inter‐limb blood pressure differences in the elderly: The Northern Shanghai Study. Issue 7 (18th June 2019) - Yu, Shikai; Ji, Hongwei; Lu, Yuyan; Chen, Shanquan; Xiong, Jing; Chi, Chen; Teliewubai, Jiadela; Fan, Ximin; Blacher, Jacque; Li, Jue; Zhang, Yi; Xu, Yawei; et al.
Abstract: Whether the combination of inter‐arm and inter‐leg systolic blood pressure differences (BPDs) and ankle‐brachial index is of clinical significance remains unclear. In this study, we aimed to investigate the association of the combination of inter‐limb systolic BPDs with cardiovascular risk factors and hypertension‐mediated organ damage (HMOD). A total of 2621 elderly subjects from the Northern Shanghai Study were divided into Group A, B, and C consisting of participants with 0, 1, and ≥2 abnormal inter‐limb systolic BPDs, respectively. Comparisons of cardiovascular risk factors and parameters of cardiac, vascular, and renal damage between groups and logistic regression models were conducted. The proportions of subjects presenting 0, 1, and ≥2 abnormal inter‐limb systolic BPDs were 60.9%, 25.1%, and 14.0%, respectively. Upward trends, from Group A, through Group B, to Group C, were observed for the level or prevalence of nearly all cardiovascular risk factors and HMOD ( P for trend ≤0.007 for all). In multiple logistic regression, Group C showed significantly higher odds for carotid plaque (vs Group A: Odds ratio [OR] = 1.88, 95% confidence interval [CI] = 1.43‐2.48; vs Group B: OR = 1.46, 95% CI = 1.08‐1.97), arterial stiffness (vs Group A: OR = 1.26, 95% CI = 0.96‐1.65; vs Group B: OR = 1.36, 95% CI = 1.01‐1.83), and left ventricular hypertrophy (vs Group A: OR = 1.35, 95% CI = 1.04‐1.76; vs Group B: OR = 1.25, 95% CI = 0.93‐1.67), when compared with Group A and B. In conclusion, the combination of abnormal inter‐limb systolic BPDs significantly associates with greater burden of cardiovascular risk factors and higher likelihood for HMOD, especially carotid plaque, arterial stiffness, and left ventricular hypertrophy.